2014
DOI: 10.1111/jace.12964
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Domain Structure Observation and Giant Magnetoelectric Coupling for PMNPT/Terfenol‐D Multiferroic Composites

Abstract: In situ observations of ferroelectric domain structure evolution, and magnetoelectric (ME) coupling are investigated for PMN‐28PT/Terfenol‐D (abbreviation of Pb(Mg1/3Nb2/3)O3‐28PbTiO3/Tb0.3Dy0.7Fe2) and PMN‐33PT/Terfenol‐D composites under the magnetic loadings. The composite of PMN‐33PT/Terfenol‐D shows stronger ME coupling than that in PMN‐28PT/Terfenol‐D. At a thickness of 0.10–0.12 mm for the single crystal plate, a giant magnetoelectric coefficient (αME) up to 2 V/cm·Oe is obtained for PMN‐33PT/Terfenol‐D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Regular domain bands appear in M-phase regions, which are in consistence with many previous studies. 16,21,24,25,30,31 However, irregular domain boundaries also appear in M-phase regions, as the morphology of the domain structure is related with the lowest energy state. 21 Examination on Figure 5A and B reveals that the adjacent domains labeled as "A" and "B" have a phase contrast of 180°.…”
Section: Pfm Analysis Of M C Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Regular domain bands appear in M-phase regions, which are in consistence with many previous studies. 16,21,24,25,30,31 However, irregular domain boundaries also appear in M-phase regions, as the morphology of the domain structure is related with the lowest energy state. 21 Examination on Figure 5A and B reveals that the adjacent domains labeled as "A" and "B" have a phase contrast of 180°.…”
Section: Pfm Analysis Of M C Phasementioning
confidence: 99%
“…For characterization of ferroelectric domain or domain boundary structures, a variety of techniques have been employed, such as X-ray and neutron diffraction techniques, 15,22 transmission electron microscopy (TEM), 19 polarized light microscopy (PLM), 16,[23][24][25] and PFM. [25][26][27][28] Using PFM, Zeng et al 26 Although PFM is capable of revealing the domain morphologies in nanoscale, and measuring the piezoelectric response of individual domains simultaneously, it is unable to detect the phase symmetry of the ferroelectric domains.…”
Section: Introductionmentioning
confidence: 99%
“…However, this value is much lower than the [100]-oriented counterpart, which is 2V/cm·Oe. 29 For composites of PMN-28PT/Terfenol-D and PMN-33PT/Terfenol-D, the different ME coupling behavior depends on the piezoelectricity of PMN-28PT and PMN-33 PT single crystals. Supposing σ is the stress transfer between the Terfenol-D plate and the PMN-PT single crystal, the ME coefficient α ME of the composites can be evaluated from 29 Where d 31,p is the piezoelectric constant of the single crystal with the induced polarization in the thickness direction upon the applied longitudinal stress.…”
Section: Resultsmentioning
confidence: 96%
“…Recently, the authors observed the polarization rotation from R to M A for [001]-oriented PMN-28PT/Terfenol-D composite, and from O to M C and then to R for the [001]-oriented PMN-33PT/Terfenol-D composite under the applied magnetic loadings. 29 The later possesses a magnetoelectric coefficient (α ME ) up to 2 V/cm·Oe at a static magnetic field of 200 Oe and 1 kHz of the alternating magnetic field. 29 By using piezoresponse force microscopy, Miao et al 30 reported the magnetic-field-induced ferroelectric polarization reversal in bilayer Terfenol-D/PMN-33PT composite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation